Activity Based Costing and Cost Recovery Rate of Ureteroscopy Under Indonesia's INA-CBGs Payment System - Arina Manasikana; Chriswardani Suryawati; Puji Harto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Universal Health Coverage (UHC) sustainability in Low-and Middle-Income Countries (LMICs) hinges on adequate Diagnosis-Related Group (DRG) tariffs, which frequently fail to cover the true cost of complex, high-technology procedures. This study aimed to estimate the actual unit cost of 360 Ureteroscopy (URS) encounters (January-December 2023) using Activity-Based Costing (ABC) and assess the resultant Cost Recovery Rate (CRR) under Indonesia's INA-CBGs payment system. A retrospective descriptive quantitative design cost analysis was performed at RSI Sultan Agung Semarang. The ABC unit cost ranged from IDR 9.322.737 (Class I) to IDR 8.322.737 (Class III). Compared to the INA-CBGs tariff, a significant and consistent deficit was found exclusively in Class III procedures, yielding the lowest CRR of 69%. The deficit was primarily driven by high expenditure on imported consumables and Operating Room time. Conclusion and Contribution: The INA-CBGs tariff is structurally inadequate for high-severity URS cases, threatening hospital financial sustainability. This study provides the first ABC micro-costing evidence linked to INA-CBGs for urological procedures, offering critical data to policymakers for a targeted tariff review and enabling hospital management to optimize key cost drivers Keywords: Diagnosis-Related Groups, Activity-Based Costing (ABC), Cost Recovery Rate (CRR), Ureteroscopy (URS), Universal Health Coverage (UHC), Unit Cost